Adubação fosfatada, biofertilizante bovino e bacillus sp. no desempenho agronômico da cultura do amendoim sob estresse salino - Oliveira, Girna dos Santos (2024)
Peanut (Arachis hypogaea L.) is an important agricultural crop in Brazil, considered one of the most important cultivated oilseeds. The use of fertilizer-solubilizing bacteria can mitigate salt stress. The objective of this study was to evaluate gas exchange, growth and production of peanut crops irrigated with brackish water under phosphate fertilizer and inoculated with bacteria of the genus Bacillus sp. The experimental design used in this study was completely randomized, in a 4 x 2 x 2 factorial scheme, with 5 replications, referring to the forms of fertilization (F1 - 0% phosphorus, F2 - 50% phosphorus, F3 - 100% phosphorus and F4 - biofertilizer), presence and absence of the inoculant and two levels of electrical conductivity of the irrigation water (ECa – 0.3 and 4.0 dS m-1). Fertilization with organic fertilizer (100% biofertilizer) and mineral fertilizer (50 and 100% phosphorus) associated with Bacillus sp. mitigated the damage caused by saline stress and promoted greater efficiency in water use, chlorophyll index, internal CO2 concentration and stem diameter. The control treatment (without phosphate fertilizer and without salt stress) and the application of Bacillus sp. promoted greater performance in net photosynthesis, transpiration rate, stomatal conductance and plant height in peanuts. The use of bovine biofertilizer associated with the use of Bacillus sp. mitigated saline stress and provided greater performance in pod length, total pod number and peanut crop production. Fertilization forms with 50% and 100% of the recommended doses of phosphorus, associated with the use of Bacillus sp. were more efficient for pod length, pod mass and production when irrigated with water of lower salinity.